Formation of an Angular Aromatic Polyketide from a Linear Anthrene Precursor via Oxidative Rearrangement. Issue 7 (20th July 2017) - Gao, Guixi; Liu, Xiangyang; Xu, Min; Wang, Yemin; Zhang, Fei; Xu, Lijun; Lv, Jin; Long, Qingshan; Kang, Qianjin; Ou, Hong-Yu; Wang, Ying; Rohr, Jürgen; et al.
Summary: Bacterial aromatic polyketides are a group of natural products synthesized by polyketide synthases (PKSs) that show diverse structures and biological activities. They are structurally subclassified into linear, angular, and discoid aromatic polyketides, the formation of which is commonly determined by the shaping and folding of the poly-β-keto intermediates under the concerted actions of the minimal PKSs, cyclases and ketoreductases. Murayaquinone, found in several streptomycetes, possesses an unusual tricyclic angular aromatic polyketide core containing a 9, 10-phenanthraquinone. In this study, genes essential for murayaquinone biosynthesis were identified, and a linear anthraoxirene intermediate was discovered. A unique biosynthetic model for the angular aromatic polyketide formation was discovered and confirmed through in vivo and in vitro studies. Three oxidoreductases, MrqO3, MrqO6, and MrqO7, were identified to catalyze the conversion of the linear aromatic polyketide intermediate into the final angularly arranged framework, which exemplifies a novel strategy for the biosynthesis of angular aromatic polyketides. Graphical Abstract: Highlights: Identification of the entire murayaquinone biosynthetic gene cluster Anthrene-type model compounds were identified from biosynthetic mutants A linear 1(4 H )-anthracenone epoxide is key intermediate for murayaquinone formation Three oxidoreductases catalyze skeleton rearrangement of the tricyclic intermediate Abstract : Gao et al. discovered the formation of an angular 9, 10-phenanthraquinone antibiotic from a linear tricyclic intermediate via oxidative rearrangement by three oxidoreductases, MrqO7, MrqO6, and MrqO3, proving a novel strategy for the biosynthesis of angular aromatic polyketides in nature.